OS CONHECIMENTOS BÁSICOS DE CONTABILIDADE E ÁREAS AFINS: UM ESTUDO NAS UNIVERSIDADES POTIGUARES À LUZ DO CURRÍCULO MUNDIAL - Kamila Kelly Paiva de Miranda Ferreira (Universidade Federal de Santa Catarina, 2017)
This study aims to present an overview of the content taught at Rio Grande do Norteuniversities, in light of the Global Curriculum proposed by the UN/UNCTAD/ISAR. In orderto do that, the syllabus of each course at the universities underwent documentary research andcontent analyses; both elective and core courses were investigated. At this juncture, a quali-quantitative approach was adopted for data analysis, once we conducted a category-basedanalysis of the syllabi and utilized the study of the level of adherence of the PedagogicalProject of the Course to the Global Curriculum. It is important to note that out of the 17certifiedhigher learning institutions on the e-MEC Portal, only those which offered in-personcourses and were actual universities were singled out for analysis. Regarding the gathereddata, it could be observed that there are analogies between the contents that are taught inpublic (μ = 27%) and private universities (μ = 18%), mainly concerning the Basic Accountingcourse (21,83%). Also, it could be perceived that elective courses have an influence on thedistribution of the curricular activities available at theinstitutions and that, in general, theresults differ among the ones that were analyzed. This further denotes the need to reassesscurricular contents at the universities of Rio Grande do Norte so as to align these contentswith those of the Global Curriculum and have the modules taught in Accounting Schoolsconverge.